Chalcogen Bonds: How to Characterize Them in Solution?. Issue 4 (22nd November 2022) - Pale, Patrick; Mamane, Victor
Abstract: Chalcogen bonds (ChBs) occur between molecules containing Lewis acidic chalcogen substituents and Lewis bases. Recently, ChB emerged as a pivotal interaction in solution‐based applications such as anion recognition, anion transport and catalysis. However, before moving to applications, the involvement of ChB must be established in solution. In this Concept article, we provide a brief review of the currently available experimental investigations of ChB in solution. Abstract : The detection of the chalcogen bond (ChB) in solution is a prerequisite for its use in solution‐based applications. The current analytical methods used to establish ChB in solution and to quantify its strength are highlighted in this Concept article.